Konsep Kecerdasan Emosional dan Spiritual dalam Tinjauan Al-Quran dan Hadits - Sukring Sukring (Al-Liqo: Jurnal Pendidikan Islam, 2022)
Western writers have argued that scientific research is more than enough. So then that is transcendental, and religious, as well as the belief in the afterlife was considered something normative and empirical, beyond scientific rationality. Western perspective assesses that the intellectual and spiritual mental simply a reality of brain activity has nothing to do with aktivtas God. Even their research related to transcendent values ​​and absolute more emphasis on the fields of empirical, scientific rational course. Over the years the people of the world fascinated with the discovery of intelligence (IQ) of man that a person's success is determined by the intelligence of the brain. Semnetara Islamic literatures prove that intelligence is found in the western world there are already 14 centuries ago, with the revelation (Quran) to the Prophet Muhammad. Nor in the traditions, have been found in the Qur'an and Prophetic traditions. By telling the Qur'an and hadith shows a variety of human intelligence that is ruhaniyah contained in man like al-aql, al-Qalb al-nafs, and al-ruh. Intelligences that humans have a sleeping giant power a few hundred years. After scientists study the Koran and the Hadith then discovered the intelligence of the modern age.